Integrated transcriptomics and metabolomics to explore the mechanisms of Elaeagnus mollis diels seed viability decline - Ren Ruifen; Guo Jiayi; Ji Zhe; Du Shuhui; Yang Xiuyun (BMC Genomics)
Abstract Elaeagnus mollis Diels, is a rare and endangered woody plant endemic to China, which is listed on the IUCN Red List. In the natural state, the viability of its seeds declines very rapidly, which is the key to its endangered status, but the mechanism of E. mollis seed viability decline is still unclear. In order to explore the physiological and molecular mechanism of viability decline of E. mollis seeds, this study used fresh seeds as a control to compare and analyze the changes of seed vitality, antioxidant system, transcription and metabolomics, when seeds were stored for 1 and 3 months at room temperature. The viability of E. mollis seed decreased continuously after 1 month and 3 months of storage. The activities of superoxide dismutase (SOD), monodehydroascorbate reductase (MDHAR), ascorbate (AsA), and glutathione (GSH) decreased significantly, while catalase (CAT) activity increased gradually during the decline of seed viability. Transcriptomic results showed that a total of 801 differentially expressed genes (DEGs) were identified between fresh and 1-month-stored seeds, while 1,524 were identified between fresh and 3-month-stored seeds. Among them, the expression of CAT, MDHAR, GSH and GR were consistent with the results of physiological indicators. Moreover, WRKY, C3H, bZIP, B3, bHLH, NAC and AP2 / ERF-ERF transcription factors are important in regulating seed viability. Metabolomics results showed that the types of differential accumulated metabolites (DAMs) during viability decline were mainly flavonoids, amino acids and derivatives, and phenolic acids. The combined analysis results of transcriptomics and metabolomics further showed that DEGs and DAMs associated with viability were co-enriched in flavonoid biosynthesis and tryptophan metabolism pathways. Also identified were 22 key antioxidant genes, including CAT, ALDH, CHS and C4H, which were identified as participating in the changes of seed viability. This also illustrated that the metabolic pathways of flavonoid biosynthesis and tryptophan metabolism were involved in regulating the decline of seed viability by acting on the antioxidant system. These findings provide new insights into the mechanism of seed viability decline of E. mollis.